Overview of Child Development Age 3-4 Years Viewed from Mother's Knowledge About Growth and Development in the Village: Gambaran Perkembangan Anak Usia 3-4 Tahun Ditinjau dari Pengetahuan Ibu Tentang Tumbuh Kembang di Desa - Tafhamin, Tafhamin; Widowati, Hesty (Indonesian Journal of Innovation Studies, 2021)
Development is an increase in the ability of the structure, function of the body to be more complex in a regular pattern. Based on initial data obtained at PAUD Muslimat in Petung Village in January 2020 by conducting the KPSP test as many as 7 out of 10 children the results were dubious. The research design is descriptive, the population and samples of all mothers who have children aged 3-4 years are 35 people. The data are presented in the form of frequency distribution tables and cross tabulations and then analyzed descriptively without statistical tests using research data and supporting theories. The results showed that most (60%) mother's knowledge was good, most (57.2%) child development was doubtful, appropriate child development (86.7%) was more in mothers who had good and sufficient knowledge than those with less knowledge ( 60%) questionable child development. The conclusion of appropriate child development is more in mothers who have good and sufficient knowledge than those with less knowledge.